Isolation, Characterization, and Biotechnological Potential of Native Microalgae From the Peruvian Amazon - Cobos Ruiz, Marianela (2019)
The objective of this chapter is to provide scientific information on basic aspects to be taken into account to achieve the successful isolation, biochemical, and molecular characterization and then to evaluate the biotechnological potential of native microalgae of the Peruvian Amazon. Recent investigations reported by our research team has demonstrated that the isolated native microalgae from the Peruvian Amazon have a great potential for the biotechnological production of biodiesel and nutraceuticals. This biotechnological potential was identified thanks to the application of various protocols that were standardized by the authors over the last 5 years. In conclusion, the native microalgae of the Peruvian Amazon have biotechnological potential and are therefore promising for the production of both biodiesel and nutraceuticals. Various species of microalgae were identified, isolated, cultured, and characterized using biochemical, nutraceutical, and molecular techniques, the isolation stage being the starting point to achieve various biotechnological applications. Ankistrodesmus sp. is one of the microalgae with potential for the production of biodiesel and microalgae such as Haematococcus pluvialis, Scenedesmus sp., and Chlorella sp., among others demonstrated a high potential for nutraceutical production. The stress conditions to which microalgae are subjected are being a determining factor for the production of biodiesel and nutraceuticals.